Determination of the Parameters of the Aggregate Rotation Working Body Combined With a Pump Retainer between the Row of B Analysis of Experimental Research Conducted On - Abidjanovich, Moydinov Dilyorbek; ugli, Erkinov Ikromjon Bakhromjon; ugli, Makhammadjonov Zohidullo Ulugbek (American Journal of Biodiversity, 2025)
This study is devoted to the study and analysis of the design and technological parameters of a combined aggregate-rotary working element that collects cotton between rows. In horticulture, important units are high-quality inter-row cultivation, improvement of air and moisture content of the soil, as well as increasing the yield of agricultural crops. The study analyzes the geometry of the rotary cutter, its rotation speed, work productivity, mechanical impact on the soil and optimal operating modes. Recommendations on the design, choice of materials and ergonomics of the working element will also be developed. The operating parameters of the rotary working element are analyzed using computer modeling and laboratory tests taking into account the mechanical properties of the soil. The research results will serve as a basis for developing modern mechanized technologies that will allow for the efficient cultivation of row crops in horticulture. At the same time, these results can be used in the production processes and modernization of agricultural units.